Epistemology and Politics in Earth System Modeling: Historical Perspectives. (20th May 2019) - Heymann, Matthias; Dahan Dalmedico, Amy
Abstract: This commentary provides a critical account of Earth system modeling history. It argues that Earth system modeling is not simply a domain of science but also a form of politics. Earth system science carries the ideas and social and cultural norms of the peculiar historical eras in which it emerged and grew. Systems thinking and a strong belief in the power of modeling have its roots in the early Cold War era. When the Cold War era gave way to a time characterized by economic stagnation, social unrest, and rising environmentalism, climate science absorbed the new cultural trend of environmental concern, while retaining an optimism and enthusiasm in the modeling paradigm. The post‐1990s era reveals particularly clearly the political power that climate scientists unleashed. The modeling paradigm assumed hegemonic status, seized economic and social processes, and created not only scientific knowledge but also conceptions of political management of the Earth. The modeling paradigm, once a scientific strategy largely in the hands of scientists, has turned into a political agent in its own right, beyond the full control of the scientific community. Key Points: Earth system modeling initially thrived in a Cold War environment emphasizing prediction and control of the atmosphere The environmental era introduced a new massive challenge to Earth system modeling: its politicization and demands for long‐term climate prediction More recently, Earth system models have become political agents and led to a problematic convergence of Earth system science and climate governance